Three Handwritten Trinity Collections about Scribes and Ignoramuses, 15th — 16th Centuries - Anatoly S. Demin (Studia Litterarum)
Attitude to books and reading in the Old Russia is a popular topic in different studies, especially in the introductions to the Old Russian original works, and there is not much to add here. This essay however develops a new approach: it examines excerpts concerning book reading in the structure of the Old Russian manuscript collections of the 15th — 16th centuries. So far, we confine ourselves mainly to the 16th century, since previous centuries are quite scarce of material while the subsequent 17th century is, on the contrary, too rich. The article analyzes three collections of one manuscript from the funds of Russian State Library and the library of the Trinity Lavra of St. Sergius. It discusses the structure of three handwritten collections: RSL, Troitsk, and The Main col. no 748, 678, and 793. What unites them is one minor yet interesting feature — we call it “philological.” While focusing on the aforementioned collections, the essay overall covers 13 collections in comparative perspective: RSL and Troitsk. no 188, 292, 203, 678, 748, 756, 784, 793; Volokolamsk. no. 476; Moscow Spiritual Academy no 46, 95, 198 and NNB, Sofiisk, no 1376. The appendix includes excerpts about book reading from the examined collections.